Access to Education: Specific Analysis of People with Disabilities (Kanun: Jurnal Undang-undang Malaysia, 2024)
According to the World Health Organization or ‘WHO’, a person’s environment has a significant impact on their experience and level of disability. Inaccessible environments create barriers that prevent the full and effective participation of people with disabilities (PWDs) in society on an equal basis with others. Therefore, it is important to give PWDs full access to education to guarantee they have the right opportunities provided to succeed in life as others. Problems arise when the disabled have various obstacles in gaining access to formal education. Therefore, the objective of this study is to identify the definition and division of the category of PWDs, to analyse the rights of the disabled to education based on domestic and international laws, to consider proposed steps to improve the education system for PWDs and to compare the approach of jurisprudential figures to the principle of equality. These objectives are achieved through a doctrinal approach. The method used to collect and study information in completing this writing is the library-based study method. The primary sources referred to are legal statutes such as acts, national constitutions and others. Secondary reference sources that will be studied include scientific books, articles, journals and newspaper clippings. Online databases are also used as a reference such as Research Gate to obtain the latest information related to this study. Thus, this research paper will study in more depth the type of access required by those with disabilities as well as provide recommendations that can be considered by Malaysia after reviewing education systems in other countries that successfully provide full access to students with disabilities.Keywords: Disabled people, education, law, reasonable adjustment, jurisprudence, suggestions for improvementFull text: PDF